Hydrochromic carbon dots as smart sensors for water sensing in organic solvents. Issue 11 (16th October 2019) - Senthamizhan, Anitha; Fragouli, Despina; Balusamy, Brabu; Patil, Bhushan; Palei, Milan; Sabella, Stefania; Uyar, Tamer; Athanassiou, Athanassia
Abstract : The present study highlights the potential of using hydrochromic carbon dots as probes for sensing water contamination in organic solvents. Abstract : Smart, stimuli-responsive, photoluminescent materials that undergo a visually perceptible emission color change in the presence of an external stimulus have long been attractive for use in sensor platforms. When the stimulus is the presence of water, the materials that undergo changes in their light emission properties are called hydrochromic and they can be used for the development of sensors to detect and quantify the water content in organic solvents, which is fundamental for laboratory safety and numerous industrial applications. Herein, we demonstrate the preparation of structurally different carbon dots with tunable emission wavelengths via a simple carbonization approach under controlled temperature and time, involving commercial brown sugar as a starting material. The detailed experimental analysis reveals the "structure-hydrochromic property" relationship of the carbon dots and assesses their capability as effective water sensors. The carbon dots that were proved most efficient for the specific application were then used to identify the presence of water in various aprotic and protic organic solvents via a sensing mechanism based either on the fluorescence wavelength shift or on the fluorescence intensity enhancement, respectively, attributed to the formation of intermolecular hydrogen bonds between carbon dots and water molecules. This is the first demonstration of structurally defined carbon dots in a specific application. The developed carbon dots, apart from being environmentally friendly, were proved to also be biocompatible, enabling this presented process to be a path to "green" sensors.